2017
DOI: 10.1002/hep4.1019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a sodium‐glucose cotransporter 2 inhibitor in nonalcoholic fatty liver disease complicated by diabetes mellitus: Preliminary prospective study based on serial liver biopsies

Abstract: A prospective study based on serial liver biopsies was performed to investigate the efficacy of sodium‐glucose cotransporter 2 inhibitor for nonalcoholic fatty liver disease complicated with type 2 diabetes mellitus. Conclusion: Treatment for 24 weeks resulted in improvement in histopathologic features in all 5 patients. (Hepatology Communications 2017;1:46–52)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 26 publications
9
105
1
3
Order By: Relevance
“…In contrast, antidiabetic agents affect the pathophysiology of NASH. Pioglitazone, GLP-1RA and SGLT2i are expected to improve inflammation and fibrosis of NASH [35][36][37][38] . However, in the present study, the relationship between liver fibrosis markers and antidiabetic agents, such as GLP-1RA and SGLT2i, were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, antidiabetic agents affect the pathophysiology of NASH. Pioglitazone, GLP-1RA and SGLT2i are expected to improve inflammation and fibrosis of NASH [35][36][37][38] . However, in the present study, the relationship between liver fibrosis markers and antidiabetic agents, such as GLP-1RA and SGLT2i, were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that the levels of serum microRNA‐122 (miR‐122) were particularly associated with histopathological severity of liver disease and the risk of developing metabolic syndrome and type 2 DM . Our first study found that serum miR‐122 might be useful for the early prediction of histological improvement of NAFLD by SGLT2I . MicroRNAs are secreted by various lipid‐containing vesicles, including exosomes, microvesicles, and apoptotic bodies.…”
Section: Introductionmentioning
confidence: 86%
“…In our recent first report, a preliminary prospective study based on serial liver biopsies was undertaken to investigate the efficacy of SGLT2I for NAFLD complicated with type 2 DM. Treatment for 24 weeks resulted in improvement in histopathological features in all five patients …”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, SGLT2 inhibitors have become promising therapeutic agents in NASH and NAFLD patients. Several pilot studies have found a significant reduction in transaminase activity, body weight, the fatty liver index, and liver histology (steatosis and fibrosis) in NAFLD patients [50][51][52][53][54][55]. Two open randomized controlled trials (RCTs) have been performed in Japan to compare the efficacy of SGLT2 inhibitor with other oral diabetic agents, including pioglitazone and metformin.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%